2021
DOI: 10.3389/fpsyg.2021.579700
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Omnivores and Vegetarians in Personality Profiles, Values, and Empathy: A Systematic Review

Abstract: Numerous medical studies have documented vegetarian diets as having various health benefits. Studies have also compared vegetarians with other dietary groups from a socio-psychological perspective. The objective of this review is to investigate the differences between vegetarians and omnivores in terms of their personality profiles, values, and empathy skills. A search was conducted across three electronic databases. Non-randomized, observational, cross-sectional, and cohort studies were eligible. Outcomes pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 99 publications
(234 reference statements)
3
22
0
Order By: Relevance
“…The present study follows a recent systematic review by Holler et al (21) on differences between omnivores and vegetarians in which it was concluded that further studies about vegetarianism are needed-also in relation to adherents of meat-reduced diets. The current work also follows one of the suggestions for future research we have made in previous studies (10,14), namely, to explore further how and to what extent meat abstainers differ from meat lovers and flexitarians.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The present study follows a recent systematic review by Holler et al (21) on differences between omnivores and vegetarians in which it was concluded that further studies about vegetarianism are needed-also in relation to adherents of meat-reduced diets. The current work also follows one of the suggestions for future research we have made in previous studies (10,14), namely, to explore further how and to what extent meat abstainers differ from meat lovers and flexitarians.…”
Section: Introductionmentioning
confidence: 84%
“…But particularly in recent years scholarly interest in comparing vegetarians, vegans, flexitarians, and omnivores has gained traction and turned into a blossoming field of study (21,(31)(32)(33)(34)(35)(36)(37)(38). The goal of the current study is to add to this field of research by deepening our understanding in what characteristics particularly differentiate these dietary groups.…”
Section: Frontiers Inmentioning
confidence: 99%
“…Also, in one study from Poland 35 , higher levels of conscientiousness fostered positive changes in health behaviors of patients with metabolic syndrome, and these changes were in terms of correct dietary habits, physical activity, good sleep patterns, and avoiding stressful events or situations evoking strong emotions. Finally, a systematic review reported that vegetarians were more open to new experiences than their omnivore peers 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Avoidance of certain foodstuffs may also stimulate creativity because many dishes will now have to be prepared differently, e.g., without sugar, fat or gluten, which requires rethinking and reorganising. But rigid adherence to these virtues has a negative side as well: individuals with (tendencies to) eating disorders or obsessive-compulsive disorders (OCDs) may be primarily attracted by forms of diet change that require a high degree of discipline and renunciation ( 131 , 132 ). Eating disorders or OCDs may be triggered or reinforced in this manner and lead to an NE.…”
Section: Hypotheses On Psychosocial Context Effects In Diet Changesmentioning
confidence: 99%